Influence of the number of bleaching sessions on fracture resistance and dentin microhardness of endodontically treated teeth - Garrido, Lorena D. M. A. [UNESP]; Kuga, Milton C. [UNESP]; Kalatzis-Sousa, Natália G. [UNESP]; Dantas, Andrea A. R. [UNESP]; Tonetto, Mateus R.; Leonardo, Renato D. T. [UNESP]; Jordão-Basso, Keren C. F. [UNESP]; Lima, Suellen L.; Borges, Alvaro H.; Bandeca, Matheus C. (Jaypee Brothers Medical Publishing, 2017)
Objectives: To evaluate the effects of number of bleaching sessions on fracture resistance and dentin microhardness in endodontically treated teeth using 15% hydrogen peroxide with titanium dioxide nanoparticles (15HPTiO2) associated to light emitting diode (LED)–laser system. Materials and methods: Forty human incisors were endodontically treated and divided according to the number of bleaching sessions (n = 10, each group): G1 – no treatment G2 – one; G3 – two; and G4 – three sessions. The 15HPTiO2 was applied within the pulp chamber and on the buccal surface, then photoactivated using LED–laser. All experimental specimens were restored with ionomer glass cement between each session and in the final treatment. Specimens were then subjected to the fracture resistance test (kN), using an electromechanical machine. To the dentin microhardness evaluation, 40 crown extracted endodontically treated human teeth were longitudinally sectioned, divided into groups as previously described (n = 10), and submitted to similar bleaching protocol. Dentin microhardness was evaluated before and after the final dental bleaching session in each group using Knoop indentator. Data were analyzed by analysis of variance (ANOVA) and Tukey tests (p = 0.05). Results: The fracture resistance values were similar among all groups (p > 0.05). The number of dental bleaching sessions had a negative influence on the microhardness dentin, because G4 > G3 > G2 > G1 (p < 0.05). Conclusion: The number of bleaching sessions using 15% hydrogen peroxide with titanium dioxide nanoparticles associated to LED–laser system had no influence on the fracture resistance of the endodontically treated teeth crowns, but promoted a reduction in dentin microhardness.
Keywords: Dental bleaching; Dentin; Endodontics; Hydrogen peroxide; Lasers